Association of health-risk behaviors with perceived academic performance among middle and high school students: A cross-sectional study in Shanghai, China. - Chunyan Luo; Xuelai Wang; Yanting Yang; Qiong Yan; Lijing Sun; Dongling Yang (PLoS ONE, 2023)
Adolescence is a susceptible period to establish health-risk behaviors, which may have an impact on academic performance. The aim of this study was to investigate the association between health-risk behaviors (HRBs) and perceived academic performance (PAP) of adolescents in Shanghai, China. The data of the present study included three-round Shanghai Youth Health-risk Behavior Survey (SYHBS). This cross-sectional survey investigated multiple HRBs of students involved in dietary behaviors, physical activity and sedentary behaviors, intentional and unintentional injury behaviors, and substance abuse behaviors, as well as PAP by using self-reported questionnaire. Using a multistage random sampling method, 40,593 middle and high school students aged 12 to 18 years were involved. Only participants with complete data on HRBs information, academic performance and covariates were included. A total of 35,740 participants were involved in analysis. We used ordinal logistic regression to analyze the association between each HRB and PAP adjusting for sociodemographic, family environment and duration of extracurricular study. The results showed that students who did not eat breakfast or drink milk everyday were more likely to have a lower PAP, with a decreased odds of 0.89 (95%CI: 0.86-0.93, P<0.001) and 0.82 (95%CI: 0.79-0.85, P<0.001), respectively. The similar association was also found in students who did exercise ≥60 minutes for less than 5 days/week, spend time on watch TV beyond 3 hours/day and other sedentary behaviors. Most intentional and unintentional injuries, and ever smoked were associated with a lower PAP. Our finding suggests that multiple HRBs negatively associated with PAP of adolescents. It needs to raise public health concerns with HRBs in adolescents, and to develop and implement comprehensive interventions on HRBs.